Chaos theory and post-structuralism in Mr Nobody (2009) / Deanna Ishak - Ishak, Deanna (Faculty of Film, Theatre and Animation, 2016)
This academic exercise is based on Jaco Van Dormael’s Mr Nobody (2009), regarding a mathematical study known as chaos theory that is portrayed in the narration of the film. The study explores to see what chaos theory through the context of cinema and explores on how it engages in film. Using a qualitative approach, where I have utilized library and online research, this study focuses on the significance of chaos theory and analyses how the its application in film conforms to post-structuralism. Through this, I intend to incorporate chaos theory into the post-structuralist view as a mean of new exploration in film studies. As a result, I have analysed the scenes in Mr Nobody and broken them down into five main points of trigger for chaos theory; the points where each action in an initial sensitive condition have led to different consequences that moves the film. However, I have been unable to find a distinct similarity that connects chaos theory to post-structuralism.